Endodontic Treatment Of A Tooth With Change Of Diagnosis From Pulp Necrosis To Irreversible Pulpitis - Syifa Byandra; Fajar Fatriadi (Interdental Jurnal Kedokteran Gigi (IJKG), 2024)
Introduction: Dental caries is the primary cause of pulp disease. As caries progresses, the pulp undergoes morphological and histological changes. To detect pulp conditions, pulp vitality tests can be performed to stimulate myelin nerve fibers in the pulp tissue. Case: A 31-year-old female patient came to RSGM Universitas Padjadjaran with a complaint of a large cavity in the upper right front jaw tooth since a year ago. A few months later, she fell from a motorcycle which caused the cavity to become even larger. The patient had a history of spontaneous throbbing pain, but it is now completely gone.  Case Treatment: A root canal treatment was performed over six visits. The first visit involved initial examination and status recording. The second visit included caries removal, access opening, and pulp extirpation. The third visit encompassed re-walling, working length measurement, and root canal preparation. The fourth visit involved sterilization control and trial obturation. The fifth visit included obturation or filling of the root canal of tooth 11. The sixth visit consisted of obturation verification. Discussion: Accurate pulp diagnosis based on neurovascular changes within the pulp is crucial for the success of endodontic treatment. Pulp vitality tests such as cold pulp test (CPT), hot pulp test (HPT), and electric pulp test (EPT) are common methods for assessing pulp condition. Conclusion and Suggestions: To obtain a more comprehensive understanding of pulp vitality, it is necessary to use a combination of various vitality tests.